Pendekatan Diagnostik, Faktor Risiko, dan Tatalaksana Neuropati Diabetik - Muhammad Labib MY Bima; Fidha Rahmayani; Hanna Mutiara (CV. Jasa Sukses Abadi, 2023)
Diabetic neuropathy is the most common complication of diabetes mellitus. As many 25% of people with diabetes mellitus in the world and 54% in Indonesia suffer from diabetic neuropathy. Electro-diagnostic studies are best used for the diagnosis of diabetic neuropathy. In addition, the diagnosis can be made by scoring Diabetic Neuropathy Symptom (DNS) and Diabetic Neuropathy Examination (DNE). Patients with diabetes mellitus must pay attention to risk factors such as carbohydrate intake, physical activity, duration of suffering, and medication adherence to prevent complications of diabetic neuropathy. Management of diabetic neuropathy can be done with drugs or other supportive therapy. This article uses a literature review method from various national and international journal references with the following search keywords: prevalence, diagnosis, risk factors, and management of diabetic neuropathy.